Parity in bacterial communities and resistomes: Microplastic and natural organic particles in the Tyrrhenian Sea - Di Cesare, Andrea (2024)
Petroleum-based microplastic particles (MPs) are carriers of antimicrobial resistance genes (ARGs) in aquatic environments, influencing the selection and spread of antimicrobial resistance. This research characterized MP and natural organic particle (NOP) bacterial communities and resistomes in the Tyrrhenian Sea, a region impacted by plastic pollution and climate change. MP and NOP bacterial communities were similar but different from the free-living planktonic communities. Likewise, MP and NOP ARG abundances were similar but different (higher) from the planktonic communities. MP and NOP metagenome-assembled genomes contained ARGs associated with mobile genetic elements and exhibited co-occurrence with metal resistance genes. Overall, these findings show that MPs and NOPs harbor potential pathogenic and antimicrobial resistant bacteria, which can aid in the spread of antimicrobial resistance. Further, petroleum-based MPs do not represent novel ecological niches for allochthonous bacteria; rather, they synergize with NOPs, collectively facilitating the spread of antimicrobial resistance in marine ecosystems.